Cystic Fibrosis in a Female Infant with Cardiac, Ocular, and Musculoskeletal Anomalies - Azhar Farooqui; Susan Gamal Eldin; Muna Dawood Ali; Ali AlTalhi; Ahmad AlDigheari (Hindawi Limited, 2015)
Cystic fibrosis (CF) remains the most common hereditary disease in the western population. Its concomitant presence with other congenital abnormalities is a rare phenomenon with very little documentation. In this case report we describe a case of cystic fibrosis in a female infant with cardiac, ocular, and musculoskeletal abnormalities. A brief literature review is also provided.